Flozins - modern treatment for patients with type 2 diabetes - Augustyn, Dominik; Pawlikowski, Krzysztof; Korpalski, Michał; Żygłowicz, Marek; Marciniak, Mateusz; Torbicki, Adam; Gaworek, Piotr; Pawluczyk, Maria; Trybuła, Alicja (Quality in Sport, 2025)
Introduction: Type 2 diabetes is a metabolic disease characterized by elevated blood glucose levels. Uncontrolled disease leads to many complications that significantly affect quality of life and life expectancy. Flozins – sodium-glucose cotransporter 2 (SGLT2) inhibitors are a new group of drugs used in the treatment of DM 2, which, in addition to their hypoglycemic effect in the form of increased glucose excretion in urine, also have a beneficial effect on the cardiovascular system. Objective: The aim of the study was to present the benefits of using SGLT2 inhibitors in patients with type 2 diabetes. Materials and methods: We reviewed the literature in PubMed using the keywords: “Diabetes type 2”, “Flozins”, “SGLT2 inhibitors”, “Cardiovascular disease”, and “Renal disease”. Results: It has been proven that SGLT2 inhibitors, in addition to their hypoglycemic effect, also have a beneficial effect on other systems. The studies discussed show that SGLT2 drugs reduce cardiovascular risk and have a protective effect on the kidneys. Summary: The efficacy of SGLT2 inhibitors therapy has been confirmed in clinical trials. Future studies should aim to determine at what stage treatment should be initiated in order to maximize the benefits for the patient.